2022
DOI: 10.3390/electronics11193029
|View full text |Cite
|
Sign up to set email alerts
|

Secure Mimo Communication System with Frequency Hopping Aided OFDM-DCSK Modulation

Abstract: In this paper, a multiple-input multiple-output (MIMO) communication system with frequency hopping (FH) aided orthogonal frequency division multiplexing differential chaotic shift keying (OFDM-DCSK) modulation is proposed. Our objective is to improve the security of MIMO communication system which is encoded by space time block coding (STBC). In order to combat the eavesdropping or malicious attacks due to the broadcast characteristics of wireless communication system, we propose to use DCSK and FH modules to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…and (17) where ρ = Var x 2 k , it can be readily shown that all the covariance terms are zero. Thus, using the Formula (17), we may simplify (14) to…”
Section: Bit Error Rate Analysis Of Rsst-sr-dcsk Systemmentioning
confidence: 99%
“…and (17) where ρ = Var x 2 k , it can be readily shown that all the covariance terms are zero. Thus, using the Formula (17), we may simplify (14) to…”
Section: Bit Error Rate Analysis Of Rsst-sr-dcsk Systemmentioning
confidence: 99%
“…In order to combat the eavesdropping or malicious attacks due to the broadcast characteristics of wireless communication system, a MIMO communication system assisted by FH−OFDM−DCSK is designed [11] to advance the security of the MIMO communication system. A multi-user OFDM-DCSK system reduces the integration complexity of the system and improves the spectral efficiency [12].…”
Section: Introductionmentioning
confidence: 99%